Pengaruh Work Overload dan Motivasi terhadap Kinerja (Studi pada Karyawan PT. Marinal Indo Prima Jumiang Pamekasan) - Moh Khairil Anwar; Iriani Ismail (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
Companies reach the goals through their employees performance. Employees performance can affect the profits of companies. If the employees performance is low, it is difficult for the company to achieve the goals. So, the companies always try to maintain and improve the performance of their employees. The aims this study are determine the effect of Work Overload and Motivation on performance at PT. Marinal Indo Prima Jumiang Pamekasan partially. This study uses quantitative methods, simple random sampling technique as a sampling technique and a number of 51 employees as respondents. Using the multiple linear regression analysis, the results showed that the Work Overload variable partially has a significant effect on employees performance of PT. Marinal Indo Prima Jumiang Pamekasan is 0.614. The tcount is 2,700 ttable is 1,677 and the significance value is 0.010 0.05. While the Motivation variable partially has a significant effect on employees performance of PT. Marinal Indo Prima Jumiang Pamekasan is 0.354. The tcount is 3,516 ttable is 1,677 and the significance value is 0.001 0.05.